Signs of the Seasons: A New England Phenology Program - Stancioff, Esperanza; Bisson, Beth; Randall, Sara; Muhlin, Jessica; McDonough, Caitlin; Gallo, Susan (Maine Policy Review, 2017)
As global climate records continue to break, average New England air temperature increases are among the highest in the continental United States, and sea surface temperatures in the Gulf of Maine have increased faster than 99 percent of the rest of the world’s oceans. Little is known about how marine and upland biota respond to these environmental changes. Citizen science is being used to document and compare current phenology (the timing of life cycle events) for individual species with historically documented relationships between temperature changes and the onset of particular phenophases, such as leafout or gamete release. Signs of the Seasons (SOS) is a citizen science–driven phenology-monitoring program in northern New England that observes 19 upland and coastal indicator species and was developed by University of Maine Cooperative Extension, Maine Sea Grant, and partnering research scientists. This article provides an overview of SOS structure, research partnerships, lessons learned, challenges, and next steps.